Community Users in Academic Libraries: Data-Mining for Fund-Raising - Dole, Wanda V.; Hill, J. B. (Qualitative and Quantitative Methods in Libraries; 2014: Special Issue: Social Justice, Social Inclusion, 2017)
The purpose of this paper is to report the third phase of a study on the impact of one North American academic library’s extending library privileges gratis to community users. The paper reports results of an appeals letter sent to community users at the University of Arkansas at Little Rock (UALR) USA. The letter was sent to solicit donations and to study the correlation between community users’ receiving library privileges and donating. Although community users said that they value the services the Library extended to them and were more likely to donate money (Dole and Hill, 2012), few did donate as a result of the appeals letter. This paper reports on the responses of community users at one North American academic library and may or may not provide guidance for other libraries contemplating approaching community users for donations.  The results of this study may or may not be generalizable to all academic libraries.